Korzystanie z funduszy Unii Europejskiej przez jednostkę samorządu terytorialnego na przykładzie miasta Łodzi - Bury, Agata (The Use of European Union Funds by the Unit of Local Self-Government, on the Example of Łódź, 2007)
Łódź is the second biggest city in Poland. The budget is about 2 milliard zl. For several years the sources of European Union Funds have been one of its revenues. They are: PHARE - educational projects, ISPA - projects of environmental protection, European Regional Development Fund - projects of roads, of revitality of cities, European Social Fund - cultural, educational and innovational projects, as well as "Socrates-Comenius" and "Leonardo da Vinci".
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 541-552